Sentimental tales - Zoshchenko, Mikhail, 1895-1958 (Russian library (Columbia University. Press), 2018)
Mikhail Zoshchenko's Sentimental Tales are satirical portraits of small-town characters on the fringes of Soviet society in the first decade of Bolshevik rule. The tales are narrated by one Kolenkorov, who is anything but a model Soviet author: not only is he still attached to the era of the old regime, he is also, quite simply, not a very good writer. Shaped by Zoshchenko's masterful hands--he takes credit for editing the tales in a series of comic prefaces--Kolenkorov's prose is beautifully mangled, full of stylistic infelicities, overloaded flights of metaphor, tortured cliché, and misused bureaucratese, in the tradition of Gogol. Yet beneath Kolenkorov's intrusive narration and sublime blathering, the stories are genuinely moving. They tell tales of unrequited love and amorous misadventures among down-on-their-luck musicians, provincial damsels, aspiring poets, and liberal aristocrats hopelessly out of place in the new Russia, against a backdrop of overcrowded apartments, scheming, and daydreaming. Zoshchenko's deadpan style and sly ventriloquy mask a biting critique of Soviet life--and perhaps life in general. An original perspective on Soviet society in the 1920s and simply uproariously funny, Sentimental Tales at last shows Anglophone readers why Zoshchenko is considered among the greatest humorists of the Soviet era.